Risk and protective factors for the neuropsychomotor development of babies from the perspective of the sustainable development goals (Revista Contexto & Saúde, 2025)
This research approached 4- to 18-month-old children who attended daycare centers aiming to identify their neuropsychomotor development (NPMD) and home stimulation and verify the association of neonatal, socioeconomic, and environmental variables with NPMD, from the perspective of the sustainable development goals (SDGs). Cross-sectional study in 181 children, assessing their NPMD (Alberta Infant Motor Scale – AIMS and Denver II screening test) and contexts (Affordances in the Home Environment for Motor Development Infant Scale – AHEMD-IS). The data were analyzed with chi-square independence tests. The NPMD of 45.3% of the children were at risk/delayed; 31.5% had little home stimulation. There was an association with NPMD perceived as typical by parents (p=0.005), who were 7.5 times more likely to correctly identify NPMD. There was an association with maternal educational attainment (p=0.011); mothers with lower educational attainment were up to 3.8 times more likely to have at-risk babies. Better AHMED-IS Physical Space (p=0.006), Variety of Stimulation, and Total scores (p
Keywords: Child; Sustainable Development Goals; Child Day Care Centers; Risk Factores; Child Deveopment